Evaluation of encapsulated rejuvenators conventionally used for asphalt self-healing enhancement as architected cellular particles - Traseira Piñeiro, Laura (2024)
Recent advancements in pavement engineering have introduced innovative materials and methods to enhance asphalt performance and promote road sustainability. Among these, encapsulated asphalt rejuvenators are gaining attention for their potential to extend the lifespan of pavements by promoting asphalt’s self-healing capabilities. Asphalts containing this type of additive are regarded as smart materials, as the capsules, that are added to the asphalt during the mixing process, progressively release the bitumen rejuvenator in response to traffic loading. Thus, bitumen ageing, which causes asphalt to become stiffer and prone to cracking, can be controlled, and the binder regains its ability to flow and close any microcracks, preventing asphalt cracking.